GSDMD contributes to myocardial reperfusion injury by regulating pyroptosis - Ye, Xiaomiao; Zhang, Peng; Zhang, Yuting; Luan, Jingyun; Xu, Caili; Wu, Zhengyu; Ju, Dianwen; Hu, Wei (Frontiers in Immunology, 2022)
Background Gasdermin D (GSDMD) plays an essential role in the pathway of pyroptosis. However, whether GSDMD participates in myocardial ischaemia/reperfusion injury (MI/RI) remains poorly understood. Methods Serum levels of GSDMD and IL-18 in ST-segment elevation myocardial infarction (STEMI) patients were measured by ELISA. The expression of GSDMD and GSDMD N-terminal (GSDMD-NT) in vivo and in vitro was assessed by western blot and immunofluorescence staining. GSDMD-/- mice and wild type (WT) mice were induced MI/RI, followed by cardiac ultrasound and histological analysis. Results Clinically, patients suffering from STEMI after percutaneous coronary intervention (PCI) exhibited higher levels of GSDMD and IL-18 than that in the controls. In vitro, the cleavage of GSDMD was significantly upregulated in macrophages exposed to hypoxia/reoxygenation or H2O2. In vivo, the levels of GSDMD and GSDMD-NT increased notably after MI/RI, especially in macrophages infiltrating in the infarct area. Moreover, compared with WT mice, GSDMD-/- mice showed reduced infarct size (25.45 ± 3.07% versus 36.47 ± 3.72%), improved left ventricular ejection fraction (37.71 ± 1.81% versus 29.44 ± 2.28%) and left ventricular fractional shortening (18.01 ± 0.97% versus 13.62 ± 1.15%) as well as attenuated pathological damage after I/R injury, along with reduced levels of proinflammatory cytokines and decreased infiltration of neutrophils. Conclusions Our study revealed that GSDMD deficiency significantly alleviated the inflammatory response by regulating pyroptosis, reduced the infarct size and preserved cardiac function after MI/RI, thus providing a potential strategy for the treatment of myocardial reperfusion injury.